Automating the Testing of Instrumentation Amplifiers for Clinical Applications - Davis, Matthew D.; Lovely, Dennis F. (CMBES Proceedings, 2010)
Instrumentation amplifiers are used for the measurement of many biopotential signals such as ECG, EMG and evoked potentials. Performance parameters for these devices include the differential gain, the common-mode rejection ratio (CMRR), noise performance and bandwidth. Manual testing to determine these parameters can be very time consuming, especially if a high-resolution measurement is desired. As part of our on-going development of low-noise instrumentation amplifiers for the measurement of evoked potentials, we have developed an automated measurement system to evaluate differential gain, CMRR and noise performance. The system uses a commercial signal generator and an oscilloscope coupled with a shielded custom designed test fixture. This incorporates the necessary auxiliary amplification and analog signal processing to perform the required tests. The complete test system is controlled from a PC. The control software was written using the Instrument Control Toolbox from Matlab and is based around a user-friendly GUI. This allows for easy modification of testing parameters such as frequency range and resolution. The same GUI is used for displaying the results and providing options for exporting the data for further analysis via other software or for data logging. Custom test parameters can also be saved for repeated testing of similar devices. Preliminary tests of the system have shown good results in that verification of the specifications provided by the manufacturer for several different amplifiers has been possible. It is proposed this low-cost system could be used to provide a quick and easy check on a variety of clinical instruments.